Czech Republic : Staff Report for the 2014 Article IV Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2014)
Growth is gaining momentum, led by strong external demand while domestic demand is also picking up. The central bank's foreign exchange intervention policy has helped stem deflationary pressures but inflation is still well below target. Following substantial fiscal adjustment over the past three years, an easing of the fiscal stance is underway and the new government's medium-term fiscal plans have not yet been fully elaborated. The financial system is sound and resilient to shocks, and improvements in the regulatory and supervisory architecture are ongoing. The challenge for the authorities is to create the conditions for strong and sustainable growth while maintaining macroeconomic stability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet